A ground triplet dinuclear copper(II) spiro-complex involving tetraiminoneopentane. (18th April 2017) - Kimura, Akifumi; Ishida, Takayuki
Graphical abstract: X-ray diffraction study of [Cu2 L (CF3 SO3 )4 ] (L  = tetrakis(2-pyridylmethyleneimino)neopentane) clarified that the molecular structure was topologically spiro, but the two coordination basal planes were not orthogonal with the dihedral angle of 49.8(1)°. The χ m T value of [Cu2 L (CF3 SO3 )4 ] showed a small increase on cooling below 10 K, indicating the presence of ferromagnetic coupling. Abstract: Tetrakis(2-pyridylmethyleneimino)neopentane (L ) was designed to form a spiro-structure after complex formation, whereL plays a role of a double tetradentate bridging ligand. The X-ray diffraction study of [Cu2 L (CF3 SO3 )4 ] clarified that the molecular structure was topologically spiro but the two coordination basal planes were not orthogonal with the dihedral angle of 49.8(1)°. The χ m T value of [Cu2 L (CF3 SO3 )4 ] showed a small increase on cooling below 10 K, indicating the presence of ferromagnetic coupling. Fitting to a singlet–triplet model gave 2 J / k B  = +0.293(7) K. The density-functional-theory calculation of the [Cu2 L ] 4+ core reproduced the ferromagnetic coupling. Furthermore, from another calculation after removal of the neopentyl skeleton, through-bond interaction is clarified to be major in the exchange mechanism. The intervening sp 3 -hybridized carbon atoms may be spin-polarized.